THE STATE OF VISCOELASTIC PROPERTIES OF MUSCLES IN ATHLETES WITH VISUAL IMPAIRMENT DURING THE COMPETITIVE PERIOD - Krasnoperova T.V. ,; Gavrilova M.P. ,; Bystrova M.V. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the viscoelastic properties of muscles in athletes with visual impairment of classes B1, B2 and B3 before and after running 60m during the competitive period, to determine the functional characteristics of muscles associated with training and gender. Methods and structure of the study. The study was conducted as part of the state task, during the All-Russian athletics competitions (sport of the blind) in Chelyabinsk in February 2023. Athletes with visual impairment before and after the 60 m race were measured viscoelastic properties of muscles. Measurement of myotonometry parameters of the rectus femoris muscle (RFM) and the lateral head of the gastrocnemius muscle (LHGM) was carried out using the MyotonPRO device before and after the competitive exercise. Results and conclusions. It was revealed that after running 60 meters in athletes with visual impairment of classes B1, B2 and B3, there is a tendency to reduce tone and stiffness, increase elasticity, relaxation time and fluidity. The study showed that the higher the qualification of a sprinter with visual impairment in the study group, the lower the stiffness, but the higher the relaxation time, both at rest and after running 60 m. relaxation and fluidity, and after running higher elasticity.